Building an Inclusive Society (Speech Impaired) by Applying Educational Values at TPQ Ibn Ummi Maktum - Fathallah Majed; Ariq Dzulnazmi; Nashwa Umamy; Difaul Husna (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This research aims to analyze the implementation of inclusive education at TPQ Ibnu Ummi Maktum, an Al-Quran educational institution designed to provide equal access to all individuals, including those with disabilities. Using a qualitative approach, this research explores learning methods, challenges faced, and the role of teachers in supporting the success of inclusive education. Data was collected through interviews, observation and document analysis. The research results revealed that TPQ Ibnu Maktum runs three main programs: regular classes, sign classes, and Braille classes. The learning methods applied, namely qiroah and kitabah, are designed to meet the needs of students with various limitations. Despite experiencing challenges such as limited numbers of teaching staff and lack of public awareness, TPQ has succeeded in having a positive impact, including changing society's attitudes towards inclusivity. Collaboration with various parties, including Ahmad Dahlan University, strengthens TPQ's capacity to offer inclusive education. This research recommends intensive training for teaching staff, especially for Braille classes, as well as the development of a more comprehensive curriculum to increase the effectiveness of learning for students with special needs.